Identifying chondroprotective diet-derived bioactives and investigating their synergism. Issue 1 (December 2018) - Davidson, Rose; Green, Jonathan; Gardner, Sarah; Bao, Yongping; Cassidy, Aedin; Clark, Ian
Abstract Osteoarthritis (OA) is a multifactorial disease and nutrition is a modifiable factor that may contribute to disease onset or progression. A detailed understanding of mechanisms through which diet-derived bioactive molecules function and interact in OA is needed. We profiled 96 diet-derived, mainly plant-based bioactives using anin vitro model in chondrocytes, selecting four candidates for further study. We aimed to determine synergistic interactions between bioactives that affected the expression of key genes in OA. Selected bioactives, sulforaphane, apigenin, isoliquiritigenin and luteolin, inhibited one or more interleukin-1-induced metalloproteinases implicated in OA (MMP1, MMP13, ADAMTS4, ADAMTS5 ). Isoliquiritigenin and luteolin showed reactive oxygen species scavenging activity in chondrocytes whereas sulforaphane had no effect and apigenin showed only a weak trend. Sulforaphane inhibited the IL-1/NFκB and Wnt3a/TCF/Lef pathways and increased TGFβ/Smad2/3 and BMP6/Smad1/5/8 signalling. Apigenin showed potent inhibition of the IL-1/NFκB and TGFβ/Smad2/3 pathways, whereas luteolin showed only weak inhibition of the IL-1/NFκB pathway. All four bioactives inhibited cytokine-induced aggrecan loss from cartilage tissue explants. The combination of sulforaphane and isoliquiritigenin was synergistic for inhibitingMMP13 gene expression in chondrocytes. We conclude that dietary-derived bioactives may be important modulators of cartilage homeostasis and synergistic relationships between bioactives may have an anti-inflammatory and chondroprotective role.